2016
DOI: 10.1111/adb.12473
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic alterations in the anterior cingulate cortex and related cognitive deficits in late adolescent methamphetamine users

Abstract: The adolescent brain, with ongoing prefrontal maturation, may be more vulnerable to drug use-related neurotoxic changes as compared to the adult brain. We investigated whether the use of methamphetamine (MA), a highly addictive psychostimulant, during adolescence affect metabolic and cognitive functions of the anterior cingulate cortex (ACC). In adolescent MA users (n = 44) and healthy adolescents (n = 53), the levels of N-acetyl aspartate (NAA), a neuronal marker, were examined in the ACC using proton magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 51 publications
(66 reference statements)
0
24
1
1
Order By: Relevance
“…Among studies that reported group differences, higher myo- inositol levels were most reliably observed in the frontal cortex [124, 190-197]. Among studies that did not report a difference, methamphetamine/MDMA subjects tended to use less frequently than those reporting group differences [198, 201, 202, 204, 207]. …”
Section: Resultsmentioning
confidence: 99%
“…Among studies that reported group differences, higher myo- inositol levels were most reliably observed in the frontal cortex [124, 190-197]. Among studies that did not report a difference, methamphetamine/MDMA subjects tended to use less frequently than those reporting group differences [198, 201, 202, 204, 207]. …”
Section: Resultsmentioning
confidence: 99%
“…The Stroop task, which measures the ability to suppress irrelevant information, is one of the most commonly used tests of inhibitory control in neuropsychiatric patients. Chronic meth use is associated with poorer performance in the Stroop task in adolescents (35,37,65) and adults with meth use disorder (23,26,34,40,41,45,. Effects in adolescents suggest that reduced inhibitory control may be a predisposing factor to developing meth use disorder.…”
Section: Inhibitory Controlmentioning
confidence: 99%
“…N-acetylaspartate levels correlate with poorer attention and inhibition in adult (68) and adolescent (37) meth users, and people with schizophrenia (150)(151)(152). Interestingly, reduced N-acetylaspartate in ACC is more dramatic with early onset of meth use (37), and reduced ACC levels of N-acetylaspartate are present at the early stages of schizophrenia (149), and in highrisk offspring of schizophrenia patients (152).…”
Section: Inhibitory Controlmentioning
confidence: 99%
“…Nonetheless, findings regarding metabolite concentrations in the brains of MA users remain inconsistent. In a 1H-MRS study of 29 patients with MA addiction and 45 healthy controls, Crocker et al discovered that patients of the MA group exhibited decreased levels of glutamate ( 49 , 50 ). In contrast to our findings, one previous study involving 44 adolescent MA users and 53 healthy adolescents reported that NAA levels were lower in the anterior cingulate cortex of teenagers in the MA group.…”
Section: Discussionmentioning
confidence: 99%